Rapid visual detection of dengue virus by combining reverse transcription recombinase-aided amplification with lateral-flow dipstick assay. (June 2020) - Xiong, Yufeng; Luo, Yasha; Li, Huan; Wu, Weixiang; Ruan, Xiaolin; Mu, Xiaoping
Highlights: A novel point-of-care test for the detection of dengue virus (DENV) RNA was developed by combining reverse transcription recombinase-aided amplification (RT-RAA) with lateral-flow dipstick assay (LFD). The developed RT-RAA-LFD assay can be performed in the field or low-resource settings to rapidly detect DENV RNA at 37 °C within 30 minutes. The detection limit of the RT-RAA-LFD assay was 10 copies/μL and was specific, showing no cross-detection with other viruses. The RT-RAA-LFD assay offers excellent performance for the detecting dengue virus the same as RT-qPCR in a clinical setting. Abstract: Objectives: Dengue caused by infection with the dengue virus (DENV) is endemic in the tropical and subtropical regions of the world and of greatest public health concern. With more large outbreaks in rural areas, the purpose of this study was to develop a point-of-care test using recombinase-aided amplification and lateral-flow dipsticks for rapidly detecting DENV in low-resource settings. Methods: The primers for the recombinase-aided amplification (RAA) assay were designed based on 3' UTR of the DENV genome and screened. The RAA temperature, time and the concentration of primers were then optimized, as well as the lateral-flow dipstick assay (LFD) time. Finally, the diagnostic performance of the reverse transcription (RT)-RAA-LFD assay was evaluated using blood samples from 247 patients who were clinically suspected to be infected with DENV. Results: The RAA primer pair F1/R2 was the optimal combination for detecting DENV. The RT-RAA was performed in an incubator block at 37 °C for 20 minutes, and the amplicons were visible in the flow dipsticks from a naked eye within 3 minutes. The detection limit of the developed RT-RAA-LFD assay was 10 copies/μL with high specificity for DENV. Compared with commercial reverse transcription quantitative PCR assay, the kappa value of RT-RAA-LFD in the 247 clinical samples was 0.957. Conclusions: In this study, a rapid and visual point-of-care test based on RT-RAA and LFD assay was developed. It was found to be suitable for reliable detection of DENV in low-resource settings with limited laboratory capabilities and optimal storage conditions.